2019
DOI: 10.1186/s40813-018-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological considerations on African swine fever in Europe 2014–2018

Abstract: In 2007 African swine fever (ASF) arrived at a Black Sea harbour in Georgia and in 2014 the infection reached the European Union (EU), where it still expands its territory. ASF is a fatal viral disease affecting domestic pigs and wild boar of all ages with clinical presentations ranging from per-acute to chronic disease, including apparently asymptomatic courses. Until the detection of the first case inside the EU, infections in the current epidemic were mainly seen among pig farms with generally low biosecuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
343
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 264 publications
(360 citation statements)
references
References 62 publications
(52 reference statements)
7
343
0
10
Order By: Relevance
“…Overall, this indicates that on average, the spread of ASF has a moving boundary due to wild boar movement of less than 25km in a year. This is in line with statistical analysis of the cases in Europe, with estimates of spread at a rate of 2-5km/month (Chenais et al 2019) and 1.5km/month (Podgórski and Śmietanka 2018). Our estimates, which are for spread by wild boar movement only, match the lower bounds of these statistical analyses.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Overall, this indicates that on average, the spread of ASF has a moving boundary due to wild boar movement of less than 25km in a year. This is in line with statistical analysis of the cases in Europe, with estimates of spread at a rate of 2-5km/month (Chenais et al 2019) and 1.5km/month (Podgórski and Śmietanka 2018). Our estimates, which are for spread by wild boar movement only, match the lower bounds of these statistical analyses.…”
Section: Discussionsupporting
confidence: 89%
“…In one study environmental transmission due to shedding of virus from infected live boar was found to be less than 3 days (Olesen et al 2018). Chenais et al (2019) state that ASF has been found experimentally to remain infectious in forest soil for 112 days. Further, Chenais et al (2019) mentioned another study in which soil samples from carcass locations were PCR-positive "several days or weeks after the carcasses has been removed although no viable virus could be isolated".…”
Section: Parameter Valuesmentioning
confidence: 98%
See 3 more Smart Citations